Effect of Cryopreservation Conditions of Viability of Lactobacillus plantarum Probiotic - Zhelobetskaya, O. V.; Babinets, O. M.; Vysekantsev, I. P.; Ryazantsev, V. V. (Problems of Cryobiology and Cryomedicine, 2008)
There was shown the possibility of cryopreserving an industrial strain of lactic-acid bacteria Lactobacillus plantarum in sucrosegelatine medium. It has been established that when freezing bacterial concentrate (5x1011 CFU/ml) the bacteria viability did not differ from the controland it was not affected by the media compositions and cooling protocols.